Time Course of Auxin Stimulations of Growth - dela Fuente, R. K. (1970)
Measurements of the time course of growth responses of corn coleoptile sections to pulses of auxin (10(−5)m indoleacetic acid) establish that the growth rate changes in a regular pattern around the auxin pulse: a latent phase of 12 to 15 minutes is followed by an acceleration of growth rate lasting 15 to 20 minutes, after which a fairly steady rate is maintained. When the auxin source is withdrawn, there is an after-effect of about 15 minutes followed by a decay of growth rate, which reaches 50% decay after a further 15 to 40 minutes. The decay phase appears to be a function of the transport of auxin out of the sections. The 50% decay of growth for single cells is estimated at 30 minutes from the time of withdrawal of an exogenous supply of auxin. The regulation of growth by auxin is rapidly imposed or dissipated as auxin enters and exits, respectively, suggesting a facile association and disassociation of auxin with a growth-limiting site in the cell. It is proposed that the growth-stimulated state is dissipated at once when the transportable auxin has passed out of the cell.